2006
DOI: 10.1002/hep.21034
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonuclease 1 aggravates acetaminophen-induced liver necrosis in male CD-1 mice

Abstract: An overdose of acetaminophen (APAP) (N-acetyl-p-aminophenol) leads to hepatocellular necrosis induced by its metabolite N-acetyl-p-benzoquinone-imine, which is generated during the metabolic phase of liver intoxication. It has been reported that DNA damage occurs during the toxic phase; however, the nucleases responsible for this effect are unknown. In this study, we analyzed the participation of the hepatic endonuclease deoxyribonuclease 1 (DNASE1) during APAP-induced hepatotoxicity by employing a Dnase1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 28 publications
3
55
1
Order By: Relevance
“…31 In models of AAP-induced liver damage, which is a major cause of human ALF, some studies showed apoptosis after drug exposure of mice and mouse hepatocytes, whereas other reports indicated that necrosis is the principal mode of liver damage. 32,33 These observations might be related to our findings. Using two independent methods, we demonstrate for the first time that Predictive discrimination of (A) caspase-generated CK-18 fragments and (B) caspase-3/7 activity as determined by receiver operating characteristics (ROC) plot analysis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…31 In models of AAP-induced liver damage, which is a major cause of human ALF, some studies showed apoptosis after drug exposure of mice and mouse hepatocytes, whereas other reports indicated that necrosis is the principal mode of liver damage. 32,33 These observations might be related to our findings. Using two independent methods, we demonstrate for the first time that Predictive discrimination of (A) caspase-generated CK-18 fragments and (B) caspase-3/7 activity as determined by receiver operating characteristics (ROC) plot analysis.…”
Section: Discussionsupporting
confidence: 81%
“…36 In models of AAP-induced cytotoxicity it was also demonstrated that nonapoptotic calcium-dependent endonucleases, such as DNase-1, mediate TUNEL reactivity and DNA fragmentation. 33 These data clearly suggest that TUNEL reactivity, which is often used to identify apoptosis but also occurs in necrosis, certainly overestimates the role of apoptosis in models of ALF. 26,27 Moreover, ATP depletion-induced necrosis resulting from severe mitochondrial dysfunction is consistent with the high lactate levels that develop in critically ill ALF patients and are associated with poor outcome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in response to stress, endonucleases become activated and are released from cellular compartments to reach nuclear DNA, thus completely destroying it within a few hours after cell injury or cell death. Therefore, inactivation of endonucleases before cell/tissue injury is usually cytoprotective (Basnakian et al, 2005;Napirei et al, 2006;Apostolov et al, 2007Apostolov et al, , 2009Apostolov et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, their participation in cell death in general after tissue injury seems crucial and evidence of this is overwhelming. Recent studies demonstrated that inactivation of the endonucleases causes protection of normal and cancer cells against a variety of injuries in vitro and in vivo Basnakian et al, 2005;Napirei et al, 2006;Yin et al, 2007), suggesting that the endonucleases are essential for and mechanistically linked to injuryrelated cell death. In addition to causing cell death itself, the endonuclease are certainly essential for clean up after cell death, removal of DNA from blood plasma, and destroying "foreign" DNA from bacteria and viruses consumed by cells (Buzder et al, 2009).…”
Section: Cytotoxic Endonucleases In Normal Prostate and Prostate Cancmentioning
confidence: 99%